The Effect of the Project-Based Learning Model on Creativity Achievements in Early Childhood - Afriani, Nurul Annisa; Syamsuardi; Intisari; Nur Alim Amri; Heni Safitri Hasbur (Universitas Pendidikan Ganesha, 2025)
Children's creativity, especially in combining colors, shapes, and textures, as well as their ability to experiment and explore, is not yet optimal. This problem arises due to inappropriate and less interesting learning methods. This research aims to analyze the effect of applying the project-based learning (PjBL) model on increasing creativity in early childhood. This research uses quantitative methods with a pre-experimental design in the form of a pre-test and a post-test for one group. The research population was 30 children, with a sample of 15 children selected using purposive sampling techniques. Data were collected through observation using validated guidelines. Hypothesis testing was performed using nonparametric analysis, Wilcoxon test with a significance level of 0.05. The results showed a significant increase in creativity in children, with the average score increasing from 23.93 in the pre-test to 49.07 in the post-test. Statistical analysis shows a significance value of 0.001 (<0.05), indicating that applying the PjBL learning model has a positive effect on the creativity of young children. These results reflect that children's ability to combine visual elements creatively, solve problems in a simple way, and experiment increased after applying the PjBL model. This research concludes that PjBL can be an innovative solution in supporting the development of creativity in early childhood, especially in the context of learning centered on exploration and direct experience. These results recommend the widespread use of PjBL to increase children's creativity in various early childhood education institutions.